Bureaucracy from the Human Rights Perspective and Its Effect on Public Service - Akmal, Akmal; Muchtar, Henni (Journal of Moral and Civic Education, 2018)
The aim of this study is to find out the bureaucracy models from Human rights perspective as one of regional government public service influential factors, which is the influence of unprofessional work of civil servants (Abuse of power), the ignorance on duty (Violation by omission) and wrong policies which violated public rights (Violation by commissions) toward public services by regional government of South Pesisir Regency which is led to neglect of public services. Orientation on the interests of the bureaucracy which is shown by a large budgetaround 70% to 30% for the bureaucracy and the people. The study uses a quantitative approach, conducted in the of South Pesisir Regency with 200,000 households and a population of 1,000 households’ sample into respondents. Data were collected through questionnaires that have been validated and processed through techniques Path-Analysis with SPSS version 16. The results prove that the variables: human rights-minded bureaucracy (professional, caring not negligence), and humane policies is related to andinfluencial means to public service. Model hypothetical designed proven can be used as a model of bureaucracy in the public service vision of human rights, can improve citizen satisfaction with the services provided by the district government. The results of this study can serve as a model that needs to be tested in wider area, indifferent and spatial locus and cultural contextvalues, in order to make it a reliable model. Keywords: bureaucracy, human rights, abuse of power, violation by omission, violation by commission, public service Abstrak Tujuan penelitian adalah mencari model birokrasi dalam perspektif Hak Asasi Manusia sebagai faktor yang mempengaruhi pelayanan publik, yaitu pengaruh ASN yang tidak bekerja secara profesional, kelalaian dalam bertugas, dan kebijakan birokrasi yang salah. Orientasi pada kepentingan birokrasi yang ditunjukan dengan APBD yang besar 70% untuk birokrasi dan 30% untuk rakyat. Penelitian menggunakan pendekatan kuantitatif, yang dilakukan di Kabupaten Pesisir Selatan dengan 200.000 orang KK populasi dan 1.000 orang KK sampel yang menjadi respondennya. Data dikumpulkan melalui angket yang telah divalidasi dan diolah melalui teknik Path-Analysis dengan bantuan program SPSS versi 16. Hasil penelitian membuktikan bahwa variabel: birokrasi yang berwawasan HAM (professional, peduli (tidak melakukan kelalaian), dan kebijakan yang manusiawi menunjukan keterkaitan dan pengaruh yang berarti terhadap pelayanan publik. Model hipotetik yang dirancang terbukti dapat dijadikan sebuah model birokrasi dalam pelayanan publik yang berwawasan Hak Asasi Manusia, dapat meningkatkan kepuasan warga terhadap pelayanan yang disediakan pemerintah kabupaten. Hasil penelitian ini dapat dijadikan sebagai sebuah model yang perlu diuji secara lebih luas pada lokus dan konteks nilai budaya yang berbeda secara spasial, sehingga memiliki keterhandalan model. Kata kunci: birokrasi, hak asasi manusia, abuse of power, violation by omission, violation by commission, pelayanan publik